Shear Wave Elastography in Children with Portal Vein Thrombosis is not a Sensitive Predictor of Upper Gastrointestinal Bleeding: a Pilot Study - Magd Ahmed Kotb; Marwa Mohamed Onsy; Bothainah M. Abdulwahab Abduljalil; Mona Ahmed Kamel; Rania Hamdy Hashem (Cairo University, Faculty of Medicine, Department of Pediatrics, 2024)
Background: Extrahepatic portal vein thrombosis (EHPVT) is a cause of portal hypertension in children. It is complicated by upper gastrointestinal variceal bleeding. Aim of the work: to study shear wave elastography (SWE) assessed liver and spleen stiffness among children with EHPVT as a predictor of esophageal varices, its grade and/or upper gastrointestinal (GIT) bleeding. Methods: This case-control study included 18 children with EHPVT who were not secondary to liver disease and 18 healthy children as a control group who underwent ultrasonography and SWE of the liver and spleen. The patient group underwent upper GIT endoscopy as well. Results: The mean ± SD age of the children with EPVT was 9.11 ± 5.26 years, and 5 (27.7%) were females. Three (16.7%) had thrombophilia, 11 (61.1%) had undergone neonatal placement of umbilical catheter, both neonatal intensive care unit admission and thrombophilia in 2 (11.1%) and omphalitis in one (5.5%). All had clinically evident splenomegaly and sonographic evidence of portal vein cavernoma, 2 had recanalized portal vein. SWE stiffness of the right lobe was 7.39 ± 0.86 kPa, the left lobe was 7.64± 0.99 kPa and splenic stiffness was (mean± SD was 68.1 ± 22.8 kPa and range 28-121 kPa) among those with EHPVT, compared to the control group which was 6.83 ± 0.37 kPa, 7.39 ± 0.85 kPa, and (mean± SD was 19.61 ± 2.7 kPa and range 17.2-24.2 kPa), (p = 0.018), (p=0.036) and (p=0.00001) respectively. Esophageal varices bleeding and grade did not correlate with the modified caudate to right lobe diameter ratio (p=0.621), and (p= 0.53), stiffness of the right lobe (p=0.64) and (p= 0.684), left lobe (p=0.297) and (p= 0.223), or spleen stiffness (p=0.499) and (p= 0.196) respectively. Eleven (61.1%) had patent lienorenal collaterals, they were older (mean age 10± 5.3years) compared to those who did not develop (6.7 ± 3.6 years) lienorenal collaterals (p=0.06). The development of spontaneous lienorenal shunts was associated with a decreased risk of variceal bleeding (p= 0.013). Conclusion: EHPVT in children was associated with hepatic and splenic stiffness compared to the control group. The stiffness did not correlate with the upper GIT variceal grade or bleeding. The development of spontaneous lienorenal shunts seems to deflate portosystemic shunt pressure and reduce the risk of variceal bleeding.